Comparison of PANAMutyper and PNAClamp for Detecting KRAS Mutations from Patients With Malignant Pleural Effusion - CHOI, SU YEON (In Vivo, 2019)
Background/Aim: KRAS is one of the frequently mutated genes in human cancers and often relates with drug resistance and poor prognosis. PANAMutyper™ is a novel technology that integrates PNAClamp™ and PANA S-Melting™. In the present study, PANAMutyper™ and PNAClamp™ were compared for the detection of KRAS mutations using different samples of patients with malignant pleural effusion. Patients and Methods: A total of 103 patients (including 56 lung adenocarcinoma, 10 lung squamous carcinoma, 17 small cell lung cancer, 3 large cell lung cancer, 3 stomach cancer, 2 ovarian cancer, and others) with malignant pleural effusion were investigated using matched tumor tissue, cell block, and pleural effusion samples. The diagnostic performance of these two methods was compared. Results: KRAS mutations were detected in 18 (17.5%) of 103 patients using tissue, cell block, and pleural effusion samples. All 18 patients with KRAS mutations were detected by PANAMutyper™ using any sample type, however, only 7 cases were detected by PNAClamp™. Among the subtypes of KRAS mutations, substitution in codon 12, 35G>T was the most frequent, followed by substitution in codon 12, 35G>A and codon 12, 34G>A. In pleural effusion specimens, PANAMutyper™ showed a better diagnostic performance compared to PNAClamp™. Conclusion: PANAMutyper™ had a diagnostic superiority for the detection of KRAS mutations in patients with malignant pleural effusion compared to PNAClamp™, although there was a concordance between PANAMutyper™ and PNAClamp™ results. Therefore, PANAMutyper™ can be used for a more sensitive and accurate detection of KRAS mutations.